El nuevo derecho francés de los contratos - Cabrillac, Rémy (2016)
The French Civil Code on contract law was not renewed since 1804, so law enforcement was questioned due to it was not adapted to the requirements in a globalized world, and the constant economic and socia lchanges. In this article, the author analyzes the implications of the reform of contract law in France, which was influenced by two drafts. This reform has two characteristic features, which are the economic and social needs. About the first point –the economic needs–, these are evident in the contractual organization and flexibility. On the second point –the social needs–, these are evident in the protection of the weaker party, and the application of the theory of improvidence. In this way, contract law adapts to the demands of the twenty-first century.